Distributed and Flexible workflow coordination using defeasible logic programming - PV, Sakeer (2007)
This is an exploration to foretell a future in which traditional approaches for developing workflow management systems can be supplanted by new techniques and emerging technologies. This thesis recommends sets of methodologies for performing multiagent-based distributed and flexible workflow systems. Its objective is to deal with some of the present issues in the traditional workflow system from the business point of view. This thesis proposes that the traditional design of workflow management systems (clientserver) could be replaced by a defeasible logic programming (DeLP) engine-based multiagent platform that is more flexible and can better replicate workflow’s distributed characteristics in the open environment. This thesis presents sets of technologies for enacting multiagent-based distributed and flexible workflow systems. Its purpose is to tackle some of the existing problems in the traditional workflow system from the business point of view. This thesis proposes that the conventional system architecture of workflow management systems (client-erver) could be replaced by a defeasible logic programming (DeLP) engine–based multiagent platform that is more open and collaborative, and can better reflect workflow’s distributed features in the open environment. This system also eliminates the requirement for centralized workflow coordination and proposes to build a flexible and distributed workflow management system using a multiagent system on a java agent development (JADE) framework, where the workflow semantics and business logic are built using DeLP. The main outcome of this research is to provide approaches for utilizing defeasible logic programming methodologies in application development, especially in business applications, where DeLP can contribute much for the automation of business logic. Moreover, a multiagent system on a JADE framework helps to maximize the use of existing process models and tools for automation of business processes. The model implemented as part of this thesis confirms that a workflow framework using DeLP improves the adaptability and decentralization of workflow management.